A new species of the lenticel fungal genus Claviradulomyces (Ostropales) from the Brazilian Atlantic forest tree Xylopia sericea (Annonaceae) - Robert W. Barreto; Peter R. Johnston; Pedro W. Crous; Harry C. Evans (IMA Fungus, 2012)
Claviradulomyces xylopiae sp. nov. is introduced for a fungus occurring in association with abnormal (enlarged, spongy) lenticels of Xylopia sericea (Annonaceae), a common tree of the Atlantic forest and Cerrado ecosystems in Brazil. This is the second species described in the genus and, although it is morphologically distinct from the type species, C. dabeicola from West Africa, it possesses the same characteristics. Apothecial ascomata have periphysoids and paraphyses that are inflated apically (clavate), and ornamented with denticles (raduliform). Furthermore, similar to the type species, it also has long-cylindric or acerose, aseptate ascospores and conidia. An additional asexual morph was produced in culture and is described. Molecular studies of C. dabeicola and the new species confirmed a placement in Ostropales, although a relationship to Odontotremataceae was not supported. Both species were consistently in association with abnormal lenticular development on their woody hosts. It remains to be ascertained, however, if these are the causal agents of the bark disorders, or, simply, opportunistic colonisers. The finding of the second species in the genus Claviradulomyces on a plant from a distantly related family to that of the host of C. dabeicola (Erythroxylaceae) for the genus on a different continent suggests that fungi in this genus may be common on lenticels of other woody plants, and could even have a pantropical distribution. It is possible that fungi in the genus have remained unreported until now because lenticels have remained neglected as a habitat surveyed by mycologists.